Le Québec à l'heure de la réforme du droit des sociétés (compagnies) ou le législateur schizophrène - Giguère, Marc (Les Cahiers de droit, 1984)
How can two parts (1 and 1A) of a same statute (Quebec Compagnies Act) be of a such a different spirit and at the same time complementary (part 1A needs part I to be complete and effective) and serve for years and years without the risk of severe distorsions and misleading solutions ?